(untitled) (CIPEEX, 2022)
ENVIRONMENTAL EDUCATION IS A RECURRING DISCUSSION IN SOCIETY, ESPECIALLY DUE TO THE AGGRAVATION OF SEVERAL ENVIRONMENTAL PROBLEMS THAT CURRENTLY OCCUR AROUND THE WORLD AND THE URGENCY OF CREATING A MODEL OF SOCIETY BASED ON SUSTAINABILITY. TELEVISION REPORTS, SCIENTIFIC ARTICLES, AMONG OTHER NEWS OBSERVED IN VARIOUS TYPES OF SOCIAL NETWORKS SHOW THE GREATNESS OF THIS ISSUE AND GAVE RISE TO THE INTEREST IN THIS RESEARCH. THIS PRE-PROJECT AIMS TO ANALYZE THE NEED FOR ENVIRONMENTAL EDUCATION AS A FACILITATING FACTOR IN THE INCLUSION OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN THE SANTA TEREZINHA FULL-TIME TEACHING CENTER - ITAPACI - GO. THIS INSERTION OF ENVIRONMENTAL EDUCATION WILL CONTRIBUTE TO THE INTEGRAL AND INTEGRAL DEVELOPMENT OF THESE SPECIAL STUDENTS, PROVIDING GROWTH IN THE FACE OF THEIR DIFFICULTIES AND ABILITIES IN THEIR MAIN DIMENSIONS THAT COMPOSE THEM AS CULTURAL, AFFECTIVE, SOCIAL, COGNITIVE AND AMONG OTHERS, MAKING THEM PARTICIPANTS IN SOCIETIES AND PROMOTERS OF ISSUES SÓCIO-ENVIRONMENTAL.